INNOVATIVE DESIGN AND ANALYSIS OF THE AI-POWERED GUARDIAN LAWN MOWER - Satya Sai Sanka; Vamsi Bonela; Ashok Vanjarapu; Sumanth Rachamadugu; Raghu Routhu; A. Lakshumu Naidu (The Bioscan, 2024)
The project presents " Innovative Design and Analysis of the Guardian Lawn Mower with artificial intelligence". Major advances in lawn care and home security. It includes the development of various lawnmowers designed to operate in intelligent, automatic, semi-automatic, and manual modes. The mower features independent suspension wheels, a sturdy frame with a capacity of over 100 kg, and a solar panel for natural batteries. The system includes a powerful internal generator for accurate grass collection and a lidar sensor for precise navigation and visual impact, including identifying objects and people. Sound sirens and cameras installed in the house increase home security by capturing images of strangers and sending instant notifications to phones. This project uses a Jetson Nano for operation, a Raspberry Pi for control, and a motor to independently control each wheel. Design and review using SolidWorks and ANSYS to ensure model integrity and functionality. The program not only improves lawnmower technology but also includes home security measures to meet the needs of today's society better.